Bacterial and short-chain fatty acid profiling of faecal samples - Faujan, Nur Huda (2011)
Human gastrointestinal tract consists of an extremely complex microbiota mainly the anaerobic organisms. Many studies have been done to investigate the human intestinal microbiota. The use of molecular techniques based on DNA for microbial studies is of interest due its reliability, rapid and sensitivity method. Real-time polymerase chain reaction (PCR) has become one of the most widely used methods and an important tool for analysis of bacterial quantification as well as for detection and identification of bacterial species. In this study, real-time PCR has been used to investigate and quantify bacterial species in human faecal samples. Prior to the analysis, the extraction of DNA from human faeces had been optimised to produce a high quality and yield of DNA. Based on this purpose, DNA from faecal samples was extracted using QIAamp® DNA Stool Mini Kit. However, to give maximum DNA yields, four different procedures of extraction using this kit have been modified by adding 1 mL of 1x PBS buffer in preheating step or 600 μL of 1x PBS buffer incorporated with InhibitEx (inhibitor-adsorption) tablet. Two different amounts of 20 mg/mL proteinase K (15 μL or 25 μL) were used to digest protein and remove protein contamination. From this study, results showed that the addition of 600 μL of 1x PBS buffer incorporated with the InhibitEX tablet increase removal of inhibitors in faecal samples. Addition of 25 μL of proteinase K also produced higher DNA yield compared to the addition of 15 μL of proteinase K for protein digestion. Optimisation of DNA extraction is a crucial factor in molecular analysis of faecal samples due to the presence of many inhibitors in faecal samples that can interfere with the accuracy of real-time PCR analysis. Next, specific primer based on 16S rRNA gene was used to analyse and amplify bacterial DNA from faecal samples. The specificity of all primers used were tested by conventional polymerase chain reaction (PCR). Results showed that all primers were highly specific with the target bacteria and amplified DNA with the expected PCR products size. In order to apply real-time PCR for quantitative analysis, the real-time PCR conditions have been optimised to provide an accurate analysis. Standard calibration curve for quantitative analysis was constructed using plasmid DNA. All standard calibration curves plotted from plasmid DNA produced slope between -3.84 and -3.29, which highlighted the efficiency of reaction assay between 81.8% and 101.4%. Efficiency of real-time PCR assay is a crucial factor in order to provide accurate and precise result for quantification. In order to apply real-time PCR for analysis of intestinal microbiota, faecal samples were obtained from subjects with inflammatory bowel disease (IBD) and also healthy condition. From this study, results showed that Bacteroides and B. fragilis in faecal samples of IBD patients were significantly higher (P<0.05) than that of healthy persons. The mean for Bacteroides in faecal samples of IBD patients and healthy persons were 10.9 log10 cells/g and 10.3 log10 cells/g, respectively. The mean for B. fragilis in faecal samples of IBD patients and healthy person were 5.9 log10 cells/g and 4.6 log10 cells/g, respectively. B. fragilis was not even detected in some faecal samples of healthy persons. Other bacteria such as Desulfovibrios, Clostridium coccoides, Escherichia coli and Enterococcus faecalis did not show any significant difference (P>0.05) in faecal samples between two groups of subjects. The concentration of short-chain fatty acids (SCFAs) of faecal samples in both groups was also analysed using high performance liquid chromatography (HPLC) method. The SCFAs in human colon are produced by fermentation of carbohydrates, proteins and peptides by human colonic bacteria. Results showed that acetic, butyric and propionic acids concentration was lower in faecal samples of IBD patients as compared to that of healthy persons. However, only butyric and propionic acids were significantly lower (P<0.05) in faecal samples of IBD patients as compared to that of healthy persons. The mean concentration of butyric acid in faecal samples of IBD patients was 66.2 μmol/g and in healthy person was 175.0 μmol/g. The mean concentration of propionic acid in faecal samples of IBD patients was 52.8 μmol/g and in healthy persons was 93.3 μmol/g. Results also showed that concentration of lactic acid in faecal samples of IBD patients was higher than that of healthy persons. The concentration of formic, pyruvic and isobutyric acids in faecal samples were also analysed. In faecal samples of IBD patients, the concentration of pyruvic and isobutyric acids were higher than that of healthy person but not significant (P>0.05). In conclusion, DNA extraction from faecal samples using QIAamp® DNA Stool Mini Kit with addition of 600 mL of 1x PBS buffer in removal inhibitors step and higher amount of 20 mg/mL proteinase K in eliminating contaminated protein resulted in increased quality and yield of faecal DNA. By using real-time PCR, this study showed that the composition of certain bacterial species in IBD faecal samples differed from that in faecal samples of healthy persons. The concentration of certain SCFAs also changed in faecal samples of IBD patients and which might be attributed to difference in certain bacterial species. Furthermore, this study also showed that real-time PCR assay was an efficient and rapid method for studying bacterial profile in faecal samples.